AI POWERED MARKETING: EXPLORING THE FACTORS RESPONSIBLE FOR AI ADOPTION AMONG GEN Z’S CONSUMERS IN PAKISTAN - Madiha Obaid; Dr. Sara Rashid (International Journal of Contemporary Issues in Social Sciences, 2024)
The revolution of AI has brought a drastic change in the consumer landscape. This study profound the impact of AI in Generation Z, born between 1990 and early 2010. The purpose of this study is to explore the dynamic interplay between AI applications and Generation Z’s consumer behaviour. This study examined how AI- driven innovation shaped their preferences and influence decision making processes. This study will be crucial to influence of AI application on consumers’ attitude as AI technology shape consumers perceptions, it allows strategic adaptation in marketing and communication strategies. The study covers the unique characteristics of Gen Z’s involvement with AI applications. Generation Z is the spearhead of the AI revolution in consumer behaviour, which successfully providing the platforms to engage with products, services and brands. The study aims to find out the influence of AI application in Gen Z’s consumers. The survey was conducted through questionnaire, the targeted population were Generation Z’s consumers in Pakistan, Karachi. The SPSS and Smart PLS used to analyse data.